Relación entre posicionamiento ideológico y tendencia hacia el autoritarismo en un grupo de jóvenes de 18 a 39 años de la Universidad Antonio Nariño (2019)
Political Psychology is a branch of Psychology that seeks to understand the phenomena psychological problems associated with political activities; This in a society like the Colombian one can be quite useful if one considers the growing polarization that exists on issues such as agreements of peace and the Venezuelan crisis, both have served as a reference framework to move the chips policies in both directions; In this way, citizens have taken positions that in some cases are defended authoritatively. Therefore, the main objective of this work has been to identify the relationship between the authoritarian tendency and the ideological positioning, to For this purpose, two scales were used (RWA and Ideological Self Positioning Scale) with responses Likert type, which meet the consistency requirements when validated in the context Colombian.